Endoscopic Detection of Early Esophageal Squamous Cell Carcinoma in Patients with Achalasia: Narrow-Band Imaging versus Lugol's Staining. (9th July 2013) - Ide, Edson; Carneiro, Fred Olavo Aragão Andrade; Frazão, Mariana Souza Varella; Chaves, Dalton Marques; Sallum, Rubens Antônio Aissar; de Moura, Eduardo Guimarães Hourneaux; Sakai, Paulo; Cecconello, Ivan; Maluf-Filho, Fauze
Abstract : Chromoendoscopy with Lugol's staining remains the gold standard technique for detecting superficial SCC. An alternative technique, such as narrow-band imaging (NBI), for "optical staining" would be desirable, since NBI is a simpler technique and has no known complications. In this study, we compare NBI without magnification and chromoendoscopy with Lugol's staining for detecting high-grade dysplasia and intramucosal esophageal squamous cell carcinoma (SCC) in patients with achalasia. This was a prospective observational study of 43 patients with achalasia referred to the Gastrointestinal Endoscopy Unit of the Hospital of Clinics, São Paulo, University Medical School, Brazil, from October 2006 to February 2007. Conventional examinations with white light, NBI, and Lugol staining were consecutively performed, and the suspected lesions were mapped, recorded, and sent for biopsy. The results of the three methods were compared regarding sensitivity, specificity, accuracy, positive predictive value, negative predictive value, positive likelihood value, and negative likelihood value. Of the 43 patients, one was diagnosed with esophageal squamous cell carcinoma, and it was detected by all of the methods. NBI technology without magnification has high sensitivity and negative predictive value for detecting superficial esophageal squamous cell carcinoma, and it has comparable results with those obtained with Lugol's staining.